The role of microRNAs in arterial remodelling - Nazari-Jahantigh, Maliheh; Wei, Yuanyuan; Schober, Andreas (Thrombosis and Haemostasis, 2012)
Adaptive alterations of the vessel wall architecture, called vascular remodelling, can be found in arterial hypertension, during the formation of aneurysms, in restenosis after vascular interventions, and in atherosclerosis. MicroRNAs (miR) critically affect the main cellular players in arterial remodelling and may either promote or inhibit the structural changes in the vessel wall. They regulate the phenotype of smooth muscle cells (SMCs) and control the inflammatory response in endothelial cells and macrophages. In SMCs, different sets of miRs induce either a synthetic or contractile phenotype, respectively. The conversion into a synthetic SMC phenotype is a crucial event in arterial remodelling. Therefore, reprogramming of the SMC phenotype by miR targeting can modulate the remodelling process. Furthermore, the effects of stimuli that induce remodelling, such as shear stress, angiotensin II, oxidised low-density lipoprotein, or apoptosis, on endothelial cells are mediated by miRs. The endothelial cell-specific miR-126, for example, is transferred in microvesicles from apoptotic endothelial cells and plays a protective role in atherogenesis. The inflammatory response of the innate immune system, especially through macrophages, promotes arterial remodelling. miR-155 induces the expression of inflammatory cytokines, whereas miR-146a and miR-147 are involved in the resolution phase of inflammation. However, in vivo data on the role of miRs in vascular remodelling are still scarce, which are required to test the therapeutic potential of the available, highly effective miR inhibitors.
Keywords: Atherosclerosis; macrophage; smooth muscle cells; vascular remodelling